Exploration of the Implementation of Scaffolding Strategies to Enhance Students’ Understanding of Sequences and Series - Munir, Muhammad; Ahmad, Ahmad; Dos Santos, Mariano; Rashid, Salman (JTMT: Journal Tadris Matematika, 2025)
Mathematics learning is often perceived as difficult due to its abstract nature, particularly in the topic of arithmetic sequences and series. This study aims to explore the implementation of scaffolding strategies in teaching sequences and series and to examine their impact on students’ understanding. The research employed a qualitative approach with a case study design involving 22 eleventh-grade social science students from MA Hidatul Islamiyah Bagik Nyaka. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the application of scaffolding through guiding questions, visual representations, step-by-step exercises, and direct feedback effectively enhances students’ conceptual understanding of sequences and series. Students demonstrated improved systematic thinking as well as progress in identifying patterns, understanding formulas, and solving contextual problems. Therefore, scaffolding strategies are proven to be effective in helping students grasp abstract concepts in a more concrete manner. The study recommends that teachers consistently integrate scaffolding, particularly in mathematics learning that requires a high level of conceptual understanding